Neuroinflammation in glaucoma: a myriad of cellular pathways and players - Michael MacLean; Sean D. Lydon; Cátia Gomes; Elizabeth M. Pizzi; Cory A. Diemler; Sarah E. R. Yablonski; Gareth R. Howell; Jason S. Meyer; Richard T. Libby (Mammalian Genome, 2026)
Glaucoma is a complex neurodegenerative disease with multiple subtypes, yet all are characterized by the progressive dysfunction and loss of retinal ganglion cells (RGCs), which ultimately results in vision impairment and blindness. Elevated intraocular pressure (IOP) is a major risk factor for glaucoma; however, it is neither necessary nor sufficient for glaucomatous neurodegeneration, as patients can exhibit high IOP without developing glaucoma and patients can develop glaucoma with normal IOP. Yet FDA-approved treatment options are largely limited to approaches to minimize risk and reduce IOP. Thus, there is a critical need to target other aspects of glaucoma pathophysiology. Neuroinflammation is broadly defined here as immune-relevant responses, often involving microglia and astrocytes, within the central nervous system which may include peripheral immune cell infiltration. Burgeoning evidence has implicated glia in the development and progression of glaucoma in human tissues and mouse models. Most mouse models of glaucoma to date have shown that microglia and astrocytes are reactive in early stages of glaucomatous neurodegeneration prior to overt RGC loss. However, there is growing evidence that human and mouse glia adopt distinct phenotypes in response to neurodegeneration. Thus, there is critical need to expand our studies to include the new generations of human cell culture models. In this review, we discuss: 1) the evidence of neuroinflammatory processes in human glaucoma; 2) models of glaucoma relevant neuroinflammation; and the evidence specifically for 3) innate immune cell-driven and 4) macroglia-driven processes.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Water Exchange Characteristics of Tidally Influenced Hydrilla Invasion Sites in the Lower Connecticut River - Andrew W. Howell; Benjamin P. Sperry; Jens P. Beets; Michael W. Durham; Jonathan S. Glueckert; Amber E. Riner (Estuaries and Coasts, 2026)
The Lower Connecticut River (CR) is an ecologically and recreationally significant ecosystem within New England, but the river has become increasingly vulnerable to the intrusion of aquatic invasive species (AIS) like hydrilla ( Hydrilla verticillata ). The hydrilla population recently discovered in the Lower CR is genetically unlike former hydrilla clades present in the United States. The specific biological and management components of this unique clade-C hydrilla in comparison to its cohorts remains largely undetermined and the nature of management action to combat the submersed plant within the tidally influenced lotic system further complicates waterway resilience efforts due to high-water exchange. Because of the inherent environmental challenges attributed to lotic environs, the use of aquatic herbicides remains the primary management tool for selective and effective hydrilla control. However, knowledge of the site-specific water exchange processes at infested sites coupled with subspecies- and herbicide-specific concentration-exposure time (CET) requirements are essential for successful plant management. The primary goal of the present studies was to quantify bulk water exchange rates at five representative hydrilla infestation sites within the Lower CR using Rhodamine WT dye (RWT) to mimic prospective herbicide application operations. Dye monitoring indicated distinct variability among study site water exchange rates, with RWT half-lives ranging from 0.35 to 72.36 h following application. Future management efforts deploying herbicide should consider these methods and findings when selecting appropriate herbicide active ingredients and use rates to achieve hydrilla control. While the present water exchange findings offer initial guidance, comparable dye studies will be necessary as management programs target additional hydrilla invasion areas within the river.

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

Re-assessment of a large archosaur dentary from the Late Triassic of South Wales, United Kingdom - Owain Evans; Cindy Howells; Nathan Wintle; Michael J. Benton (Proceedings of the Geologists' Association, 2025)

Application of a population status model on several recreational lake trout (Salvelinus namaycush) fisheries in Manitoba, Canada - Giulio Navarroli; Bradley E. Howell; Andrew W. R. Klein; Eric J. Mullen; Olivier Morissette; Michael D. Rennie; Caleb T. Hasler (Environmental Biology of Fishes, 2025)

Co‐Existence Slows Diversification in Experimental Populations of E. coli and P. fluorescens - Gareth Howells; Aysha L. Sezmis; Christopher Blake; Michael J. McDonald (Environmental Microbiology, 2025)
Microbes grown in heterogeneous laboratory environments can rapidly diversify into multiple, coexisting variants. While the genetic and evolutionary mechanisms of laboratory adaptive radiations are well studied, how the presence of other species alters the outcomes of diversification is less well understood. To test the effect of co‐culture growth on the Pseudomonas fluorescens SBW25 adaptive radiation, Escherichia coli and P. fluorescens were cultured in monoculture and co‐culture for 8 weeks. In P. fluorescens monoculture, Wrinkly and Smooth Spreader types rapidly evolved and were maintained over 8 weeks, while E. coli monocultures evolved two colony types, a big and a small colony variant. In contrast, we found that in co‐culture, E. coli did not evolve small colony variants. Whole genome sequencing revealed the genetic basis of possible co‐culture specific adaptations in both E. coli and P. fluorescens . Altogether, our data support that the presence of multiple species changed the outcome of adaptive radiation.

Antibacterial activity of Au(I), Pt(II), and Ir(III) biotin conjugates prepared by the iClick reaction: influence of the metal coordination sphere on the biological activity - Dominik Moreth; Lars Stevens-Cullinane; Thomas W. Rees; Victoria V. L. Müller; Adrien Pasquier; Ok-Ryul Song; Scott Warchal; Michael Howell; Jeannine Hess; Ulrich Schatzschneider (JBIC Journal of Biological Inorganic Chemistry, 2024)

Integrated multi-trophic aquaculture of steelhead trout, blue mussel and sugar kelp from a floating ocean platform - Michael Chambers; Michael Coogan; Michael Doherty; Hunt Howell (Aquaculture, 2024)

Six years of demography data for 11 reef coral species - Joshua S. Madin; Andrew H. Baird; Sean R. Connolly; Maria A. Dornelas; Mariana Álvarez‐Noriega; Michael J. McWilliam; Miguel Barbosa; Shane A. Blowes; Paulina Cetina‐Heredia; Alec P. Christie; Vivian R. Cumbo; Marcela Diaz; et al. (Ecology, 2023)
Scleractinian corals are colonial animals with a range of life‐history strategies, making up diverse species assemblages that define coral reefs. We tagged and tracked ~30 colonies from each of 11 species during seven trips spanning 6 years (2009–2015) to measure their vital rates and competitive interactions on the reef crest at Trimodal Reef, Lizard Island, Australia. Pairs of species were chosen from five growth forms in which one species of the pair was locally rare (R) and the other common (C). The sampled growth forms were massive ( Goniastrea pectinata [R] and G. retiformis [C]), digitate ( Acropora humilis [R] and A. cf. digitifera [C]), corymbose ( A. millepora [R] and A. nasuta [C]), tabular ( A. cytherea [R] and A. hyacinthus [C]) and arborescent ( A. robusta [R] and A. intermedia [C]). An extra corymbose species with intermediate abundance, A. spathulata was included when it became apparent that A. millepora was too rare on the reef crest, making the 11 species in total. The tagged colonies were visited each year in the weeks prior to spawning. During visits, two or more observers each took two or three photographs of each tagged colony from directly above and on the horizontal plane with a scale plate to track planar area. Dead or missing colonies were recorded and new colonies tagged to maintain ~30 colonies per species throughout the 6 years of the study. In addition to tracking tagged corals, 30 fragments were collected from neighboring untagged colonies of each species for counting numbers of eggs per polyp (fecundity); and fragments of untagged colonies were brought into the laboratory where spawned eggs were collected for biomass and energy measurements. We also conducted surveys at the study site to generate size structure data for each species in several of the years. Each tagged colony photograph was digitized by at least two people. Therefore, we could examine sources of error in planar area for both photographers and outliners. Competitive interactions were recorded for a subset of species by measuring the margins of tagged colony outlines interacting with neighboring corals. The study was abruptly ended by Tropical Cyclone Nathan (Category 4) that killed all but nine of the more than 300 tagged colonies in early 2015. Nonetheless, these data will be of use to other researchers interested in coral demography and coexistence, functional ecology, and parametrizing population, community, and ecosystem models. The data set is not copyright restricted, and users should cite this paper when using the data.

Influence of Preparation Conditions on Platinum and Palladium Catalysts Supported on Anodically Oxidized Stainless Steel Wire Meshes for CO Oxidation - Michael M. Royko; Savannah Howell; Ehsan Faegh; William Mustain; Jochen Lauterbach (Emission Control Science and Technology, 2021)

Beyond species counts for assessing, valuing, and conserving biodiversity: response to Wallach et al. 2019 - Ninon F. V. Meyer; Niko Balkenhol; Trishna Dutta; Maarten Hofman; Jean‐Yves Meyer; Euan G. Ritchie; Charlotte Alley; Chad Beranek; Cassandra K. Bugir; Alex Callen; Simon Clulow; Michael V. Cove; et al. (Conservation Biology, 2021)
Article impact statement : Combining native and non‐native species to evaluate biodiversity is overly simplistic and may undermine the conservation of ecosystems.

Effects of early life stress on cocaine intake in male and female rhesus macaques - Alison G. P. Wakeford; Brik Kochoian; Erin R. Siebert; Sarah Katznelson; Elyse L. Morin; Brittany R. Howell; Kai M. McCormack; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Transcriptomic analysis of hidradenitis suppurativa skin suggests roles for multiple inflammatory pathways in disease pathogenesis - Beth E. Rumberger; Erika L. Boarder; Sherry L. Owens; Michael D. Howell (Inflammation Research, 2020)

Balanced harvest: concept, policies, evidence, and management implications - Shijie Zhou; Jeppe Kolding; Serge M. Garcia; Michael J. Plank; Alida Bundy; Anthony Charles; Cecilie Hansen; Mikko Heino; Daniel Howell; Nis S. Jacobsen; David G. Reid; Jake C. Rice; et al. (Reviews in Fish Biology and Fisheries, 2019)

Effects of early life stress on cocaine self-administration in post-pubertal male and female rhesus macaques - Alison G. P. Wakeford; Elyse L. Morin; Sara N. Bramlett; Brittany R. Howell; Kai M. McCormack; Jerrold S. Meyer; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Combination of Colloidal Silicon Dioxide with Spray-Dried Solid Dispersion to Facilitate Discharge from an Agitated Dryer - Yung-Chi Lee; Michael McNevin; Craig Ikeda; Georgia Chouzouri; Justin Moser; David Harris; Logan Howell (AAPS PharmSciTech, 2019)

Correction to: Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2019)

Predicting development preferences for fishing sites among diverse anglers - Rene X. Valdez; Michael D. Drake; Conner R. Burke; M. Nils Peterson; Christopher Serenari; Andrew Howell (Urban Ecosystems, 2019)

Episodic diamond growth beneath the Kaapvaal Craton at Jwaneng Mine, Botswana - Michael U. Gress; Daniel Howell; Ingrid L. Chinn; Laura Speich; Simon C. Kohn; Quint van den Heuvel; Ellen Schulten; Anna S. M. Pals; Gareth R. Davies (Mineralogy and Petrology, 2018)

Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2018)

Test–retest reliability of two consecutive mean sleep latency tests in patients with hypersomnia - Younghoon Kwon; Louis Kazaglis; Yeilim Cho; Michael J. Howell; Mark W. Mahowald (Sleep and Biological Rhythms, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

The effect of cognitive task complexity on gait stability in adolescents following concussion - David R. Howell; Louis R. Osternig; Michael C. Koester; Li-Shan Chou (Experimental Brain Research, 2014)

Novel Mutations Mapping to the Fourth Sodium Channel Domain of Nav1.7 Result in Variable Clinical Manifestations of Primary Erythromelalgia - Roman Cregg; Bisola Laguda; Robert Werdehausen; James J. Cox; John E. Linley; Juan D. Ramirez; Istvan Bodi; Michael Markiewicz; Kevin J. Howell; Ya-Chun Chen; Karen Agnew; Henry Houlden; et al. (NeuroMolecular Medicine, 2013)

Population Pharmacokinetics and Pharmacodynamics of Ribavirin in Patients with Chronic Hepatitis C Genotype 1 Infection - Runyan Jin; Michael J. Fossler; John G. McHutchison; Charles D. Howell; Thomas C. Dowling (The AAPS Journal, 2012)

A directed miniscreen for genes involved in the Drosophila anti-parasitoid immune response - Laura Howell; Christopher J. Sampson; Miguel J. Xavier; Ekin Bolukbasi; Margarete M. S. Heck; Michael J. Williams (Immunogenetics, 2012)

Preparing for climate change in Washington State - Lara C. Whitely Binder; Jennifer Krencicki Barcelos; Derek B. Booth; Meriel Darzen; Marketa McGuire Elsner; Richard Fenske; Thomas F. Graham; Alan F. Hamlet; John Hodges-Howell; J. Elizabeth Jackson; Catherine Karr; Patrick W. Keys; et al. (Climatic Change, 2010)

The Outcome of Unintentional Pediatric Bupropion Ingestions: A NPDS Database Review - Michael C. Beuhler; Henry A. Spiller; Howell C. Sasser (Journal of Medical Toxicology, 2010)

Oxidation promotes insertion of the CLIC1 chloride intracellular channel into the membrane - Sophia C. Goodchild; Michael W. Howell; Nicole M. Cordina; Dene R. Littler; Samuel N. Breit; Paul M. G. Curmi; Louise Jennifer Brown (European Biophysics Journal, 2009)

Effects of cocaine self-administration history under limited and extended access conditions on in vivo striatal dopamine neurochemistry and acoustic startle in rhesus monkeys - Porche’ Kirkland Henry; Michael Davis; Leonard L. Howell (Psychopharmacology, 2009)

Classification tree methods for development of decision rules for botulism and cyanide poisoning - Howell Sasser; Marcy Nussbaum; Michael Beuhler; Marsha Ford (Journal of Medical Toxicology, 2008)

Interoperability of Neuroscience Modeling Software: Current Status and Future Directions - Robert C. Cannon; Marc-Oliver Gewaltig; Padraig Gleeson; Upinder S. Bhalla; Hugo Cornelis; Michael L. Hines; Fredrick W. Howell; Eilif Muller; Joel R. Stiles; Stefan Wils; Erik De Schutter (Neuroinformatics, 2007)

Development of the dopamine transporter selective RTI-336 as a pharmacotherapy for cocaine abuse - F. Ivy Carroll; James L. Howard; Leonard L. Howell; Barbara S. Fox; Michael J. Kuhar (The AAPS Journal, 2006)

How much do valley fills influence headwater streams? - Kyle J. Hartman; Michael D. Kaller; John W. Howell; John A. Sweka (Hydrobiologia, 2005)

Forage and migration habitat of loggerhead ( Caretta caretta ) and olive ridley ( Lepidochelys olivacea ) sea turtles in the central North Pacific Ocean - Jeffrey J. Polovina; George H. Balazs; Evan A. Howell; Denise M. Parker; Michael P. Seki; Peter H. Dutton (Fisheries Oceanography, 2004)
Satellite telemetry from 26 loggerhead ( Caretta caretta ) and 10 olive ridley ( Lepidochelys olivacea ) sea turtles captured and released from pelagic longline fishing gear provided information on the turtles’ position and movement in the central North Pacific. These data together with environmental data from satellite remote sensing are used to describe the oceanic habitat used by these turtles. The results indicate that loggerheads travel westward, move seasonally north and south primarily through the region 28–40°N, and occupy sea surface temperatures (SST) of 15–25°C. Their dive depth distribution indicated that they spend 40% of their time at the surface and 90% of their time at depths

Respiratory gene expression in soybean cotyledons during post-germinative development - Daniel O. Daley; Michael J. Considine; Katharine A. Howell; A. Harvey Millar; David A. Day; James Whelan (Plant Molecular Biology, 2003)